Supplementary material 1 from: Cao S, Zhang F, Zheng H, Peng F, Liu C, Zhou Q (2018) Coccomyxa greatwallensis sp. nov. (Trebouxiophyceae, Chlorophyta), a lichen epiphytic alga from Fildes Peninsula, Antarctica. PhytoKeys 110: 39-50. https://doi.org/10.3897/phytokeys.110.26961 - Cao, Shunan; Zhang, Fang; Zheng, Hongyuan; Peng, Fang; Liu, Chuanpeng; Zhou, Qiming (Zenodo, 2018)
Table S1. Pairwise distance calculated using ITS rDNA sequences :